Assembleia de aves em dois fragmentos florestais no interior do estado de São Paulo - Paes de Barros, Marcelo [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
The aim of this study was to analyze and to compare birds' communities in two forest fragments in the state of São Paulo, from qualitative and quantitative surveys. And also compare the results of the parameters studied with other works of the same nature and sampling effort and analyze the use of the bird community as environmental quality bio-indicators and state of conservation of forest fragments studied. Forest fragments were studied in the west of the state, with approximately 300 hectares, varying in shape, distance and isolation of these other fragments. The qualitative survey consisted of extensive studies in the area itself and surrounding areas, where all species of birds seen and heard were recorded and information as wealth, frequency of occurrence and similarity were recorded. But the qualitative survey was based on the methodology of counting by listening posts, which analyzed parameters such as wealth, abundance, similarity, diversity and functional groups. The field work have been developed for 12 months in each area and compared to similar works by other researchers in order to better understand the observed data. The survey showed that the number of species recorded in the Mata do Peixe fragment was higher than the Cristal fragment, and also higher than in work on bird communities in secondary forests fragments made by other authors. This fragment had a lower number of unique species and mostly treated forest species habits outlined environmental requirements. Unlike Cristal fragment, where many species have few records and mostly species are open areas and low sensitivity to environmental disturbances. It was found that the two areas suffer from forest fragmentation when presenting many species of birds living in forest edges and population imbalances in your community of birds, as poor results of detritivores birds and nectarivores. Due to the characteristics of the fragments and the comparison with similar work, ...

Este trabalho teve como objetivo analisar e comparar as assembleias de aves em dois fragmentos florestais no interior do estado de São Paulo, a partir de levantamentos qualitativos e quantitativos. E também comparar os resultados dos parâmetros estudados com outros trabalhos da mesma natureza e esforço amostral e analisar o uso da comunidade de aves como bio-indicadores da qualidade ambiental e estado de conservação dos fragmentos florestais estudados. Foram estudados dois fragmentos florestais no oeste do estado, com aproximadamente 300 hectares de área, variando em forma, distância de outros fragmentos e isolamento destes. O levantamento qualitativo se constituiu de estudos exaustivos na área propriamente dita e áreas adjacentes, onde todas as espécies de aves vistas e ouvidas foram registradas e informações como riqueza, frequência de ocorrência e similaridade foram registradas. Já o levantamento qualitativo foi realizado a partir da metodologia de contagem por pontos de escuta, onde foram analisados parâmetros como riqueza, abundância, similaridade, diversidade, abundância relativa e grupos funcionais. As coletas foram desenvolvidas por 12 meses em cada área e comparadas a trabalhos similares realizados por outros pesquisadores a fim de se compreender melhor os dados observados. O levantamento demonstrou que o número de espécies registradas no fragmento Mata do Peixe foi superior ao fragmento Cristal, e também superior em relação a trabalhos com comunidades de aves em fragmentos de florestas estacionais semideciduais realizados por outros autores. O fragmento Cristal apresentou um menor número de espécies exclusivas e sua grande maioria tratou-se de espécies de hábitos florestais com delineadas exigências ambientais. Diferente do fragmento Cristal, onde muitas espécies têm poucos registros e em sua maioria as espécies são de áreas abertas e de baixa sensibilidade à perturbações ambientais. Constatou-se...
Keywords: Ave - População; Florestas; Fragmentos florestais; Ave - Observação; Pesquisa qualitativa; Qualidade ambiental; Birds